Building the knowledge base on the social determinants of health : review of seven countries in the eastern Mediterranean region. (WHO regional publications. Eastern Mediterranean series, 2008)
In the Eastern Mediterranean Region, the knowledge base on social determinants and how these influence health is sparse. This publication reviews the social determinants of health in seven countries of the region and represents a first step towards building a knowledge base that can inform policy and strategies related to social determinants and the health inequities arising from them. The publication also discusses some of the strategies that could be adopted to forward the agenda on social determinants of health and health equity in individual countries. An EMRO Publication